2021
DOI: 10.1038/s41598-021-02391-z
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcomes of management in metastatic gastric adenocarcinoma patients

Abstract: Chemotherapy is generally considered as the main treatment for metastatic gastric adenocarcinoma. The role of gastrectomy for metastatic gastric cancer without obvious symptoms is controversial. The objective of this study is to investigate survival outcomes of treatment modalities using a real-world data setting. A retrospective cohort study was designed using the Taiwan Cancer Registry database. We identified the treatment modalities and used Kaplan–Meier estimates and Cox regressions to compare patient surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…Our current study aimed to explore the surgical treatment strategy for mGC. In-front surgery usually prevents mGC-related complications, such as bleeding, obstruction, or perforation [10,12,28]. Studies have shown that in-front palliative resection can prolong survival in select patients [10,12,29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our current study aimed to explore the surgical treatment strategy for mGC. In-front surgery usually prevents mGC-related complications, such as bleeding, obstruction, or perforation [10,12,28]. Studies have shown that in-front palliative resection can prolong survival in select patients [10,12,29].…”
Section: Discussionmentioning
confidence: 99%
“…In-front surgery usually prevents mGC-related complications, such as bleeding, obstruction, or perforation [10,12,28]. Studies have shown that in-front palliative resection can prolong survival in select patients [10,12,29]. However, chemotherapy may be interfered with, or postponed due to, surgical morbidities or surgery-related worsening of the patient's general condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, GC usually has a late diagnosis at an advanced stage, resulting in its proximity to morbidity and mortality ( Asplund et al, 2018 ). The prognosis of locally advanced gastric cancer is poor with a 5-year survival rate of 16.4% ( Katai et al, 2018 ) and median overall survival (OS) of 6–14 months in East Asia after being diagnosed from extensive clinical studies ( Hu et al, 2021 ). In contrast, if GC is diagnosed at an early stage, the 5-year survival rate is about 90% ( Saragoni et al, 2013 ), indicating the importance of early diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%